The GAGA factor regulatory network: Identification of GAGA factor associated proteins. - Dmitry Lomaev; Anna Mikhailova; Maksim Erokhin; Alexander V Shaposhnikov; James J Moresco; Tatiana Blokhina; Daniel Wolle; Tsutomu Aoki; Vladimir Ryabykh; John R Yates; Yulii V Shidlovskii; Pavel Georgiev; et al. (PLoS ONE)
The Drosophila GAGA factor (GAF) has an extraordinarily diverse set of functions that include the activation and silencing of gene expression, nucleosome organization and remodeling, higher order chromosome architecture and mitosis. One hypothesis that could account for these diverse activities is that GAF is able to interact with partners that have specific and dedicated functions. To test this possibility we used affinity purification coupled with high throughput mass spectrometry to identify GAF associated partners. Consistent with this hypothesis the GAF interacting network includes a large collection of factors and complexes that have been implicated in many different aspects of gene activity, chromosome structure and function. Moreover, we show that GAF interactions with a small subset of partners is direct; however for many others the interactions could be indirect, and depend upon intermediates that serve to diversify the functional capabilities of the GAF protein.